Isolation, identification, production and extraction of Exopolysaccharide (eps) from sea water Of tithal beach, valsad (Funded Work) - R. P. MODI,; U. D. MODI,; R. G. DESAI,; H. K. PANCHAL, (International Journal of Pharma and Bio Sciences, 2017)
Exopolysaccharides (EPS) are high molecular weight polymers which are long chain sugar residues and secreted by microorganisms into the surrounding environment. EPS shows diverse applications such as in food formulations and pharmaceutical industry, etc. Five different bacteria were isolated on Zobell marine agar medium from sea water of Valsad district, Gujarat, India and screened by using YEM (Yeast Extract Mannitol) congo red agar medium. Bacteria were identified by their morphological and biochemical characterization. Analytical method such as phenol sulfuric acid method, biuret assay, specific viscosity and molecular weight of EPS producing bacteria were carried out. The EPS was characterized by thin layer chromatography and result shown the presents of L-rhamnose, L- GlcNAC, D-ribose and D-xylose combination. Isolates of EPS producing were also studied for biofilm production in test tubes and found the potential biofilm former bacteria. Among 5 isolates studied, EPS production was highiest in colony 2.